Análise filogenética e revisão taxonômica de Xenoctenidae Ramírez & Silva-Dávila (Araneae) - Mayara Drumond Faustino Magalhães (2019)
Xenoctenidae is a small family of wandering spiders restricted to the Neotropics. The family was recently proposed based on molecular and morphological evidence, and is phylogenetically supported by the presence of a distal division in the male copulatory bulb. Four genera currently compose the family: Odo, Xenoctenus, Paravulsor and Incasoctenus. Although the creation of this family was an important step in resolving the classification of Dionycha spiders, their internal relationships still need to be studied. In this work, a phylogenetic hypothesis was proposed for Xenoctenidae. In addition, the genera that compose the family and the distribution patterns of the species were delimited. A phylogenetic analysis was performed based on parsimony, using 24 taxa and 84 morphological characters. The species of the ingroup represented exemplars of Odo and Xenoctenus. For the delimitation of distribution patterns, the consensus tree was optimized using the distribution areas of the species, classified according to the neotropical biogeographic provinces of Morrone, 2014. From the results of the analysis, the taxonomy of the genera was revised. The results of the analyzes showed that Xenoctenidae is composed of three main lines and that the species of Odo do not compose a monophyletic group. The first lineage is composed of four Brazilian species, currently described as Odo. The second lineage is composed of two species, also described as Odo, one of them being the type species of Diactenus, a genus that was synonymized with Odo. The third lineage is also composed of Odo species, in addition to all species of Xenoctenus, including the type species of both genera. In this work, the genus Incasoctenus and Paravulsor were synonymized with Odo, based on morphological characteristics described in the literature. Each of the three main lineages was here treated as a genus: the first lineage represents a new genus, called Gen1 gen. n.; the second line represents Diactenus revalidated; and the third line represents Odo (synonymized with Xenoctenus). Gen1 appears as the sister-group of all other genera and Diactenus as the sister-group of Odo. The family is distributed in Central and South America, except Amazonia. Gen1 has a restricted to the Brazilian Atlantic Forest and Diactenus occurs in Argentina, near the Andes. The Odo s.s. clade has lineages diversified between Central America and southern South America, with two species occurring in Galapagos.